X-Ray studies and magnetic properties of Ni-Cu-Zn ferrite - Rahman, M. L.; Mahmud, S. T.; Hossain, A. K. M. Akther (BRAC University, 2011)
The effect of Cu2+ on the physical and magnetic properties of Ni-Zn ferrite prepared by the auto combustion technique has been studied. From the X-ray diffraction patterns it is seen that the sample has a single phase cubic spinel structure. The bulk density, average grain size and initial permeability increase with increasing sintering temperature up to an optimum temperature. Beyond that temperature all these properties decrease.